New insights into the evolutionary dynamic and lineage divergence of gasdermin E in metazoa - Yuan, Zihao; Jiang, Shuai; Qin, Kunpeng; Sun, Li (Frontiers in Cell and Developmental Biology, 2022)
Gasdermin (GSDM) is a family of pore-forming proteins that induce pyroptosis. To date, the origin and evolution of GSDM in Metazoa remain elusive. Here, we found that GSDM emerged early in Placozoa but is absent in a large number of invertebrates. In the lower vertebrate, fish, three types of GSDME, i.e., GSDMEa, GSDMEb, and a previously unreported type (designated GSDMEc), were idenitied. Evolutionarily, the three GSDMEs are distinctly separated: GSDMEa is closely related to tetrapod GSDME; GSDMEb exists exclusively in fish; GSDMEc forms the lineage root of tetrapod GSDMA/B/C/D. GSDMEc shares conserved genomic features with and is probably the prototype of GSDMA, which we found existing in all tetrapod classes. GSDMEc displays fast evolutionary dynamics, likely as a result of genomic transposition. A cross-metazoan analysis of GSDME revealed that GSDMEa shares a conserved caspase recognition motif with the GSDME of tetrapods and cnidarians, whereas GSDMEb has a unique caspase recognition motif similar to that of mammalian GSDMD, and GSDMEc exhibits no apparent caspase recognition motif. Through functional test, four highly conserved residues in vertebrate GSDME proved to be essential to auto-inhibition. Together our results provide new insights into the origin, evolution, and function of metazoan GSDMs.